THE ROLE OF OZONATED WATER IN THE SUCCESS OF THERAPY OF CHRONIC APICAL PERIODONTITIS. CASE REPORT - Cristian Giuroiu; Raluca Dragomir; Tudor Hamburda; Mihaela Sălceanu; Liana Aminov; Anca Melian; Sorin Andrian; Maria Vataman (Romanian Society of Oral Rehabilitation, 2014)
This case report describes the achievement of endodontic space decontamination with ozonated water (conc. 20 mg mL-1, 1 min) used as canal irrigant to a central incisor from the maxilary, second quadrant, diagnosed with progressive diffuse chronic apical periodontitis. Conservative treatment of the root canal was performed in a single session. Postoperative clinical and radiological examination after 3 months revealed complete healing of periapical lesions of endodontic origin. Proper diagnosis of periapical lesions and unconventional treatment of the complex system of infected root canal allowed complete healing of the lesion without interfering through surgical endodontic therapy. This case report demonstrates the successful healing of persistent periapical lesions using an alternative (non-conventional) method with ozonated water.